2009
DOI: 10.1177/1933719108329816
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Local Over Systemic Factors in Uterine Arterial Remodeling During Pregnancy

Abstract: This study utilized a rat model in which pregnancy was surgically restricted to one uterine horn to differentiate between local (fetoplacental) and systemic (endocrine) influences on uterine vascular remodeling during pregnancy. Sprague-Dawley rats with single horn pregnancies were studied on day 20/22 of gestation and compared to age-matched non-pregnant and late pregnant controls. The morphology (axial length, lumen diameter, wall thickness) of the main uterine artery and of smaller arcuate vessels showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 28 publications
1
27
0
Order By: Relevance
“…8 Briefly, nonresorbable silk suture was used to tie off one oviduct in thirteen 8-week-old Sprague Dawley rats using routine surgical preparation and anesthesia procedure. Surgery was performed by Charles River Laboratories (CRL, Kingston, New York, and Wilmington, Massachusetts).…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Briefly, nonresorbable silk suture was used to tie off one oviduct in thirteen 8-week-old Sprague Dawley rats using routine surgical preparation and anesthesia procedure. Surgery was performed by Charles River Laboratories (CRL, Kingston, New York, and Wilmington, Massachusetts).…”
Section: Materials and Methods Animalsmentioning
confidence: 99%
“…[2][3][4][5] At the same time, circulating sex hormones and growth factors have also been shown to alter vascular structure and reactivity within the uterus of both pregnant and nonpregnant animals. [6][7][8] Many investigators have interrogated the uterine vasculature to understand how its reactivity is altered during pregnancy, and the picture that emerges is complex. Experiments have demonstrated that the smooth muscle in uterine arteries is more sensitive to adrenergic stimulation and less sensitive to nitrate signaling (eg, sodium nitroprusside, SNP); [9][10][11] conversely, endothelial cell-mediated vasodilatation is generally augmented in pregnant animals, most likely due to an upregulation of receptors, intracellular calcium signaling pathways, and vasodilator release.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that the reduced fecundity allows for compensatory increases in blood flow to the remaining fetuses, thus maintaining normal growth in the surviving pups. Although reductions in main UA and segmental artery length were both measurable and significant, these effects may be indirect, i.e., secondary to reduced pup number, as a strong positive correlation between the number of pups per uterine horn and extent of arterial elongation was noted in an earlier study in rats [27]. A similar pattern was confirmed in this study, e.g., the coefficient of determination (r 2 value) between pup number and main UA length was 0.59; thus, by definition, approximately 60% of the variability in vessel length can be accounted for by differences in pup number.…”
Section: Pregnancy and Flt1mentioning
confidence: 81%
“…This is in contrast to our data in pregnant Rln À/À mice aged 5 mo in which there was no effect of relaxin deficiency on uterine artery remodeling in either midpregnancy (Day 12.5) or late pregnancy (Day 17.5). A likely explanation is that other factors such as estrogen or local fetal influences are more important than relaxin to ensure normal uterine artery remodeling in the younger Rln À/À mice [16][17][18]. Estrogens have a direct acute vasorelaxant effect on rat uterine arteries [34] and increase local nitric oxide production either by inhibiting nitric oxide degradation [35] or enhancing endothelial nitric oxide synthase activity [36].…”
Section: Gooi Et Almentioning
confidence: 99%
“…Studies using pseudopregnant mice demonstrated that the conceptus is not involved in the initial remodeling response of the uterine artery [11], but as pregnancy progresses, the fetoplacental unit plays a major role in mediating expansion of the uteroplacental vasculature [16,17]. Shear stress resulting from an increase in blood flow velocity and estrogen both induce uterine artery remodeling by upregulating endothelial nitric oxide synthase (NOS3) [18,19].…”
Section: Introductionmentioning
confidence: 99%